Effect of austempering holding time variations of 30, 60, and 90 minutes at 300 oC on the microstructure and toughness of nodular cast iron - Darmawan, A S; Anggono, A D; Yulianto, A; Febriantoko, B W; Hamid, A (2023)
The phases of the nodular cast iron matrix are similar to those of steel. Therefore, heat treatment of steel can be applied to nodular cast iron. A potential heat treatment for nodular cast iron is austempering. This study aimed to determine the effect of austempering holding time at 300 oC on the microstructure and toughness of nodular cast iron. The austempering process begins with austenitizing at a temperature of 850 oC for 60 minutes, then the quenching process is carried out in a salt bath until a temperature of 300 oC is held with variations of 30, 60, and 90 minutes, then cooled to room temperature. Metallographic testing was conducted to determine the phase change before and after the austempering process using a Scanning Electron Microscope (SEM). Meanwhile, impact testing was carried out to determine changes in toughness before and after the austempering process. At a holding time of 30 minutes, metallographic testing on the raw material produced a gray coarse pearlite phase, black nodular graphite surrounded by white ferrite. After the austempering process, gray fine pearlite and black nodular graphite appeared. At the holding time of 60 and 90 minutes, the graphite sizes were bigger. Austempering withholding times of 30, 60, and 90 minutes resulted in impact energy of 4.2, 10, and 11 Joule. From the results of the study, it was concluded that an increase in holding time would increase the size of the graphite and the toughness of nodular cast iron. Keywords: Austempering, Nodular Cast Iron, Toughness